Tinjauan Kembali Pengaruh Tingkat Adopsi IFRS terhadap Persistensi Laba Perusahaan - Zumratul Meini (Politeknik Negeri Batam, 2020)
Globalization causes the financial and investment flows between companies and countries to increase. To facilitate interaction between companies between countries, it is felt necessary for each country to use the same financial statement standards in order to facilitate all relevant parties to be able to compare cross-country reporting. IFRS is an international financial reporting standard that can be adopted by companies in various countries, but not all countries adopt these standards. This study aims to re-analyze how the influence of the level of IFRS adoption on financial quality reports as measured by the persistence of company earnings, especially those listed on the ASEAN-5 Stock Exchange. The novelty of the research lies in the research method using a Dynamic Panel Data, which has considered the effect over time. The results of this study are expected to be used as important input for policy makers in addressing the impact of IFRS adoption on the quality of corporate financial reports.